Pengaruh Ukuran Perusahaan dan Kondisi Keuangan Perusahaan Terhadap Opini Audit Going Concern di BEI - Tanor, Linda Anita Octavia; Lontoh, Miryam P; Ulaan, Lucretia Monica (INVENTORY: JURNAL AKUNTANSI, 2024)
This study aims to examine the effect of company size and company financial condition on going concern audit opinions. This study was conducted with a population of 19 telecommunication service companies listed on the Indonesia Stock Exchange in the observation year 2019 -2022 using  the purposive sampling method with  the number of samples that meet the criteria as many as 13 companies with a total of 52 samples. The data used is in the form of audited financial statements listed and published by the Indonesia Stock Exchange through the www.idx.co.id website. The analysis method used in this study is logistic regression analysis with the Eviews Lite Student V12 tool. The results showed that the size of the company proxied using natural log assets had no significant effect on the going concern audit opinion. Meanwhile, the company's financial condition proxied using Grover's model method has a significant negative effect on the going concern audit opinion.